Adenosine-dependent regulation of paracrine factors expression in human venous blood monocytes - S. V. Ryzhov; K. S. Yuryeva; K. V. Goremykin; Ye. V. Korotkaya; I. V. Saltykova; Yu. A. Yakovleva; Ye. S. Kulikov; O. S. Fyodorova; Ye. E. Kremer; N. S. Fattakhov; A. E. Sazonov (Бюллетень сибирской медицины)
The flow cytometry analysis of human peripheral blood monocytes separated by a two step density gradient centrifugation is reported. The expression of mRNA level of adenosine receptor (AdoR) subtypes (A1, A2A, A2B and A3) and interleukin 6 (IL-6), interleukin 8 (IL-8) and vascular endothelial growth factor (VEGF) in monocytes were determined using real-time PCR. We found considerable variation across individuals in mRNA expression levels of paracrine factors after the stimulation of adenosine receptors. Our findings suggests the role of adenosinergic system accounted for interindividual differences in monocyte activation.